Javanese language learning assistance through digital media for teachers and students - Darihastining, Susi; Susilo, Jimat; Hidayat, Rahmad; Sulistyowati, Heny; Maisaroh, Siti; Chalimah, Chalimah; Faris, Ahmad (Diksi, 2023)
In the millennial era, our students are already infatuated with digital. Javanese language which is included in the local content of Junior High Schools, students are presented with local languages which have shifted a lot in usage. Students rarely use Javanese which is difficult in the form of pronunciation. The problems are (1) students in reading, writing and speaking Javanese do not understand and find it difficult to apply aspects of pronunciation and phonetics in their use. (2) the lack of interest of millennial students in preserving regional languages. (3) based on observations, today's students are lacking, mastering Javanese is called "ora njawani". And (4) the lack of teaching materials to attract students' interest, especially in the current trend, through digital. Teachers can use digital media Student Pocket Book Products which contain content from the creativity of students and teachers. In addition, students are used to using digital features. The solution to the problem of Servants is to train and assist teachers and students using digital-based learning methods and media and maintain culture. The Jombangan dictionary digital book product is used as a blended learning's medium media. This book is equipped with a barcode that contains infographic content or Javanese Jombangan YouTube content that can trigger student motivation in applying Javanese. So that students can use digital dictionaries independently and innovatively. This method can help students and teachers learn Javanese pronunciation.